The Effect of Learning Media About Healthy Snacks on Students' Knowledge and Attitudes At SDN 38 Bora, Palopo City in 2024 - Dian Furqani Hamdan; Nur Padillah (International Journal of Health and Medicine, 2025)
Background: Elementary school students have limited knowledge about healthy food, and the benefits of choosing healthy snacks. They do not understand the nutritional value of various types of food or the impact of consuming unhealthy snacks on their health. Students are often exposed to unhealthy snacks around them, such as fast food, snacks and sodas, and other less nutritious snacks. Objective: This study aims to encourage changes in students' knowledge and consumption attitudes, namely replacing unhealthy snacks with healthy snacks that are beneficial to their health. Method: This study uses a pre-experimental method, with a One Group Pre Post Test design to measure students' initial abilities before and after participating in learning activities. The population of this study was all students of SDN 38 Bora, Palopo City in 2024, totaling 151 students. The sampling method used was the Cluster Random Sampling Technique as a sampling technique, because the population was quite large, and this sampling technique is often used in various studies in the health sector, 21 respondents were obtained. Results: The study showed that the average knowledge before and after was 5.90 while the average attitude before and after was 27.76, the knowledge value p value = 0.000 ≤ 0.05 then H0 was rejected using a 95% confidence level. While the attitude value p value = 0.001 <0.05. Conclusion: there is an influence of the use of Video Learning Media on knowledge and attitudes about healthy snacks for students of SDN 38 Bora, Palopo City.